Reciprocal regulation of Yersinia pestis biofilm formation and virulence by RovM and RovA - Lei Liu (Open Biology, 2016)
RovA is known to enhance Yersinia pestis virulence by directly upregulating the psa loci. This work presents a complex gene regulatory paradigm involving the reciprocal regulatory action of RovM and RovA on the expression of biofilm and virulence genes as well as on their own genes. RovM and RovA enhance and inhibit Y. pestis biofilm production, respectively, whereas RovM represses virulence in mice. RovM directly stimulates the transcription of hmsT, hmsCDE and rovM, while indirectly enhancing hmsHFRS transcription. It also indirectly represses hmsP transcription. By contrast, RovA directly represses hmsT transcription and indirectly inhibits waaAE-coaD transcription, while RovM inhibits psaABC and psaEF transcription by directly repressing rovA transcription. rovM expression is significantly upregulated at 26°C (the temperature of the flea gut) relative to 37°C (the warm-blooded host temperature). We speculate that upregulation of rovM together with downregulation of rovA in the flea gut would promote Y. pestis biofilm formation while inhibiting virulence gene expression, leading to a more transmissible infection of this pathogen in fleas. Once the bacterium shifts to a lifestyle in the warm-blooded hosts, inhibited RovM production accompanied by recovered RovA synthesis would encourage virulence factor production and inhibit biofilm gene expression.